DNA hydroxymethylation increases the susceptibility of reactivation of methylated P16 alleles in cancer cells. Issue 6 (2nd July 2020) - Li, Paiyun; Gan, Ying; Qin, Sisi; Han, Xiao; Cui, Chenghua; Liu, Zhaojun; Zhou, Jing; Gu, Liankun; Lu, Zhe-Ming; Zhang, Baozhen; Deng, Dajun
ABSTRACT: It is well established that 5-methylcytosine (5mC) in genomic DNA of mammalian cells can be oxidized into 5-hydroxymethylcytosine (5hmC) and other derivates by DNA dioxygenase TETs. While conversion of 5mC to 5hmC plays an important role in active DNA demethylation through further oxidation steps, a certain proportion of 5hmCs remain in the genome. Although 5hmCs contribute to the flexibility of chromatin and protect bivalent promoters from hypermethylation, the direct effect of 5hmCs on gene transcription is unknown. In this present study, we have engineered a zinc-finger protein-based P16-specific DNA dioxygenase (P16-TET) to induce P16 hydroxymethylation and demethylation in cancer cells. Our results demonstrate, for the first time, that although the hydroxymethylated P16 alleles retain transcriptionally inactive, hydroxymethylation could increase the susceptibility of reactivation of methylated P16 alleles.